Theoretical Study of Ultrafast Electron Dynamics in Amino Acids. (August 2015) - Ayuso, D; Palacios, A; Decleva, P; Martín, F
Synopsis: Prompt ionization of large biological molecules may induce ultrafast charge migration along the molecular skeleton, preceding any nuclear rearrangement. This phenomenon has been recently observed in the amino acid phenylalanine in a two-color pump probe experiment, where the production of ionic fragments was measured as a function of the time delay between the two pulses and charge fluctuations manifested as sub-4.5 fs oscillations in the quantum yield of a specific doubly charged fragment. We present our latest results in glycine, and compare with previous findings in phenylalanine. We seek to perform a systematic study including larger aminoacids such as tryptophan.